Contribution of Library Professionals and Libraries in Open Educational Resources in Indian Scenario - Upneja, Sunil K (DESIDOC Journal of Library & Information Technology, 2020)
Open Educational Resources (OER) are teaching and learning content that live in public domain and are free to use or reuse. The present study examines the contribution of Library Professionals and Libraries in dealing with OERs in India. A self-designed structured questionnaire was circulated online through blogs, discussion forums, social media groups and personal e-mails among library professionals, faculty and students for random data collection. The findings of the present study reveal that though majority (93 %) of library professionals are aware of the concept of OER but they are unable to guide the OER movement because their parent institution (70 %) have no policy guidelines on design and development of OERs. Library professionals play multiple tasks in dealing with OERs, most prominent being promotion (15.63 %) and Identification (14.02 %) of OERs. The study further reveals that 25.48 per cent library professionals believe that through use of OERs the patrons get benefit of gaining access to high quality learning material. While 21.3 per cent library professionals feels that lack of awareness on the existence of OERs because of rapid technological advancement is the major challenge faced by them. The study recommends that there is an urgent need to sensitise institutions about the benefits of OER.